Corporate Governance Disclosure in Nigerian Listed Companies - Adefemi, Folashade; Hassan, Abeer; Fletcher, Mary (International Research Journal of Business Studies, 2018)
Corporate Governance Disclosure (hereafter CGD) is the extent to which an organization transparently discloses its governance practices and strategies to stakeholders (UNCTAD, 2011). This paper aims to examine the impact of corporate governance disclosure on firm performance, board composition, and company size. The study used secondary data from companies listed on the Nigerian stock exchange and examined 31 companies across 5 sectors from 2010-2013. This study used panel regression techniques and the results indicate that asset turnover, board composition and number of employees are all significantly related to corporate governance disclosure. However, return on assets, return on equity and earnings per share are not significant. Overall, this study found that listed companies compliance with the Securities Exchange Commission (SEC) Disclosure requirements has a positive influence on corporate governance performance for the firms listed in the Nigerian Stock Exchange.